Éduquer à représenter démocratiquement ? - Philippe Sahuc
Educating towards democratic representation should be a whole society stake, as seems to in crisis the political system which is the Republic groundings. In French "lycées", exists actually a pyramidal representation system including participation of young delegates to a national Council. In French farming education system, a law has just given to these youngsters the right to vote in Council. Counselling them for this function may give opportunity for an educative act towards representative democracy. Anyway, it has occurred that the previous aim to work for decoding and youths knowledge, concerning sociology, has become a route of avoidance because of establishment which decided to change without assuming all consequences connected to change. But self controlling through a simple behaviour of counseller, despite some desire to escape, is maybe in itself an education act.